(untitled) (Psychology Travelogs, 2024)
The article explores the development of professional resourcefulness among future psychologists in the context of the Russian-Ukrainian war. Drawing on theoretical frameworks and empirical research, the authors identify the main components of professional resourcefulness, including emotional intelligence and its elements, constructive coping strategies, and self-assessment of the professional development level. They highlight the importance of developing these resources through psychological training, utilizing techniques from cognitive-behavioural therapy, positive psychology, practices of emotional self-regulation and mindfulness. The authors present a training program designed to activate and enhance these professional internal resources. This study explores the effectiveness of a training program among psychology students. A quantitative and qualitative analysis was conducted to evaluate the program’s impact on participants. Results indicate significant improvements in coping strategies, emotional intelligence elements, and self-assessment of the professional development level and its components among participants. Notably, the training program demonstrated efficacy in providing psychoemotional support during societal crises and psychologically traumatic events. These findings underscore the importance of psychological training in the resource provision of the psychology students’ professional development.